Problemy współdziałania organów polskich gmin - Kotarba, Bogusław (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2016)
We współczesnych państwach istotną część zadań publicznych wykonują samorządy. Podobnie jak i w przypadku innych instytucji władzy, zadania swe wykonują za pośrednictwem organów. W artykule podjęto analizę relacji pomiędzy organami gminy – podstawowej jednostki samorządu terytorialnego. Przedstawiono, jak zmiany w prawie wpływały na pozycję i zakres kompetencji organu stanowiącego – rady gminy oraz wykonawczego − początkowo zarządu gminy, a następnie wójta (burmistrza, prezydenta). Przekładały się one również na ich wzajemne relacje. Przyjęto tezę, że współpraca organów gminy zależy nie tylko od rozwiązań instytucjonalno-prawnych, ale i od innych czynników, w tym układu sił, jaki się ukształtuje we władzach w wyniku wyborów. W oparciu o ten czynnik zaproponowano trzy modele wzajemnych relacji – idylliczny, optymalny oraz konfliktowy. Opisują one zalety i wady różnych stylów współdziałania organów gminy, które mogą się wytworzyć mimo jednakowych dla wszystkich ram prawnych.

In modern countries an important part of public duties is performed by local governments. As in the case of other institutions of power, they perform their tasks through the authorities. The article analyses the relationship between the municipal authorities – the basic unit of the local government. It shows how changes in the law affect the position and responsibilities of both the decision-making body – the municipal council, and the executive body – initially the board of the municipality, then the commune head (mayor, president). These changes also translate into mutual relations. A thesis has been assumed that the cooperation of the municipal authorities depends not only on institutional and legal solutions, but also on other factors, including the balance of power which is formed in the government after the elections. Based on this factor three models of relationships have been proposed – idyllic, optimal and confrontational. They describe the advantages and disadvantages of different styles of interactions which may appear among municipal authorities, despite identical legal frameworks for all of them.
Problem of cooperation between bodies of Polish municipalities
Keywords: samorząd terytorialny; organy gminy; rada gminy; wójt gminy; modele relacji organów gminy; local government; municipal authorities; the municipal council; commune head; models of relations among commune authorities